Determination of chlorophyll-a and its distribution in the waters of the mangrove forest rehabilitation area in Mojo Estuaria, Pemalang - Maharani, Galung Dhiva; Indarjo, Agus; Hadibarata, Tony; Zainuri, Muhammad; Endrawati, Hadi; Redjeki, Sri; Pribadi, Rudhi; Rochaddi, Baskoro; Ismanto, Aris; Jihadi, Muhammad Shulhan (Jurnal Kelautan Tropis, 2024)
Pemalang Regency has a mangrove area of around 2,839.44 but has been damaged reaching 453.38 Ha or about 16% of the existing area. This causes ecological functions in resisting abrasion, erosion, sedimentation, and carbon capture to decrease. Government efforts to restore the function of mangroves on the North Coast of Central Java carried out by rehabilitation require input from a water productivity approach. This study aims to determine the content and distribution of chlorophyll-a found in Pemalang Waters, Central Java. This was done by in situ observations in Pemalang Waters to see the fertility level of the waters, by purposive sampling at 20 sampling site, on April 30, 2024. The results obtained will be interpolated with ex situ data, including the Indonesian Earth Map (RBI), tidal data obtained from the SRGI website, flow data obtained from the Batnas website, and wind data obtained from the BMKG website. The next geospatial approach is ODV 4, Ms.Excel, and WR Plot application mapping; current analysis will be performed using ArcGIS 10.8 and Mike 21 applications; while the tidal analysis is carried out by the Admiralty method. The results of research conducted in Mojo Waters, Pemalang showed that the range of chlorophyll-a values was in the range of 1,858 - 41,287 mg / m3. The results were analyzed in sampling areas including rivers, estuaries, lagoons, eastern drift currents, western drift currents, waters still affected by estuaries, and the high seas. The distribution of chlorophyll values in these waters is the impact of nutrient supply from land because it is closely related to human activities, freshwater and seawater resuspension, drift currents, breaking waves, tidal currents. This causes the distribution pattern to occur from northeast to southwest.